The algorithm of questionnaire data analysis in sports and pedagogical researches - Denisova L.V; Usychenko V.V; Byshevets N.G (Kharkov National Pedagogical University, 2012)
Questions with the use of methods of mathematical statistics in sporting pedagogical practice are considered. The necessity of opening of maintenance and methods of unnumerical statistics is well-proven in the process of treatment of these researches of specialists on physical education and sport. The algorithm of analysis of questionnaire data is developed in sporting pedagogical researches. Basis of algorithm is made by the tables of attended. The example of realization of the offered algorithm with the use of information of the questionnaire questioning of students of higher institutes of athletic type is shown. A presence is set statistically to meaningful connection between qualification of sportsman and his persuasions about the necessity of study of information technologies.